A solid oxide fuel cell operating on liquid organic hydrogen carrier-based hydrogen – A kinetic model of the hydrogen release unit and system performance. (21st May 2019) - Peters, Roland; Deja, Robert; Fang, Qingping; Nguyen, Van Nhu; Preuster, Patrick; Blum, Ludger; Wasserscheid, Peter; Stolten, Detlef
Abstract: In this paper, a kinetic model for the catalytic dehydrogenation of perhydro dibenzyltoluene (H18-DBT), a well-established Liquid Organic Hydrogen Carrier (LOHC) compound, is presented. Kinetic parameters for hydrogen release at a Pt on alumina catalyst in a temperature range between 260 °C and 310 °C are presented. A Solid Oxide Fuel Cell (SOFC) system model was coupled to the hydrogen release from H18-DBT in order to validate the full sequence of LOHC-bound hydrogen-to-electric power. A system layout is described and investigated according to its transient operating behavior and its efficiency. We demonstrate that the maximum efficiency of LOHC-bound hydrogen-to-electricity is 45% at full load, avoiding any critical conditions for the system components. Highlights: Kinetic parameters for hydrogen release from perhydro dibenzyltoluene are presented. A coupled SOFC-LOHC energy system is described and investigated by means of a simulation. Suitable system operation and control parameters are presented.